Mixing audio : concepts, practices and tools - Izhaki, Roey (Focal Press, 2008)
"Roey Izhaki teaches you the importance of a mixing vision, how to craft and evaluate your mix, and then take it a step further. He describes the theory and the tools used, and how these are put into practice while creating mixes"--P. [4] of cover.